Data Warehouse Administration and Management - Myerson, Judith M (Enterprise Systems Integration, 2001)
Data Warehouse is a repository of integrated information, culled from any number and variety of data sources, including various databases and legacy data sources. The size of a data warehouse is usually massive and the data warehouse typically stores a wide range of information that has been generated over long periods of time. Data related to business subjects such as products, markets, and customers are all collected, integrated, and housed under the data warehouse umbrella. When this vast wealth of information is interfaced to decision support tools that offer powerful data access and analysis capabilities, the data warehouse can be fully exploited by its users.